A study on the co-combustion of rice hull and low-grade coal using a fluidized bed combustion system - Dimaguila, Stevan S. (Animo Repository, 2003)
A co-combustion tests of rice hull and low-grade coal has been carried out using a bubbling fluidized bed combustion system at the Fuel and Energy Division of Industrial Technology Development Institute, Department of Science and Technology (DOST) in Bicutan, Taguig, Metro Manila. Coal and rice hull were blended into three different ratios of 80:20, 70:20 and 60:40 with the bigger mass percentage for the rice hull. The mixture was fed through a variable speed motor screw feeder into the reactor at five different airflow rate settings and three different feed rates for each of the fuel blend mixture used. The fluidized medium was sand and the temperatures for each of the fuel blend were monitored and recorded throughout the experiment. For each of the test performed, a flue gas analysis was taken with a Kane-May combustion analyzer. The combustion efficiency was determined from the tests, resulting to a high 64.4 percent at the optimum conditions of airflow rate of 180 I/min and a feed rate of 7.6 kg/hr fuel blend mixture.